Períodes de controle de Brachiaria sp e seus reflexos na produtividade de Eucalyptus grandis - De Toledo, Roberta Estêvão Bragion; Victoria Filho, Ricardo; Bezutte, Alexandre José; Pitelli, Robinson Antonio [UNESP]; Da Costa Aguiar Alves, Pedro Luís [UNESP]; Do Valle, Celina Ferraz; Alvarenga, Sílvio Fernandes (My University, 2003)
A field trial was conduced in Piratininga, São Paulo State, Brazil, from August to 1991 to May 1999, aiming to study the effects of weed interference on the productivity of Eucalyptus grandis W. Hill Ex Maiden. The experimental design was complete randomized blocks with four replications. The treatments consisted of different extensions and times of the weed free period. The weed free periods were divided in two groups. In the first one, the weed free period were from the Eucalyptus planting to 28, 56, 112, 140, 168, 224, 278 and 360 days. In the second group the weed free period began at 0, 28, 56, 112, 140, 168, 224 and 278 days after the planting and finished at 364 days. The main weeds were Brachiaria decumbens and Brachiaria brizantha. The eucalypt plants were strong susceptive at weed interference at 12 months after planting, it was showing PAI of 12 and 6 days, when to consider 2 and 5% reduction on height. Although, to assure crop productivity at Piratininga it was necessary to maintain a weed free period of to 364 and 365 days after planting (PTPI) at 12 months, 194 and 166 days after planting at 24 months, 188 and 130 days after planting at 36 months, 88 and 54 days after planting at 48 months and 155 and 133 days after planting at 78 months, when to consider 2 an 5% reduction on heigth. But, if when to consider the DAP, the PTPI was 242 and 200 days after planting at 24 months, 208 and 153 days after planting at 36 months, 224 and 150 days after planting at 48 months and 134 and 119 days after planting at 78 months. Although when to consider the wood volume it was necessary to keep the weed free from the planting to 153 and 142 days at 36 months after planting, 99 and 91 days at 48 months after planting and 92 and 72 days at 78 months after planting (crop). However, in area to suggest the recuperation the eucalypt plants at weed Interference.
Brachiaria sp free periods and effects on the productivity of Eucalyptus grandis
Keywords: Competition; Eucalyptus; Weed management and interference; Plants (botany); Weed control; Wood; Weed management; Agriculture